2015
DOI: 10.1142/s0219622014500564
|View full text |Cite
|
Sign up to set email alerts
|

Role of Information in Decision Making of Social Agents

Abstract: The influence of additional information on the decision making of agents, who are interacting members of a society, is analyzed within the mathematical framework based on the use of quantum probabilities. The introduction of social interactions, which influence the decisions of individual agents, leads to a generalization of the quantum decision theory developed earlier by the authors for separate individuals. The generalized approach is free of the standard paradoxes of classical decision theory. This approac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 123 publications
0
28
0
Order By: Relevance
“…And it would be possible to explain the known stylized facts in financial markets, such as, for example, the fat tails of return distributions, and volatility clustering, as well as transient bubbles and crashes, which are connected with herding behavior. Some first results in that direction are reported in our previous papers [6,28], where the role of additional information, received by decision makers, is analyzed and it is shown that the amount of the additional information essentially influences the value of the quantum term. Further work on the generalization of the approach toward a dynamical theory of decision-maker societies is in progress.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…And it would be possible to explain the known stylized facts in financial markets, such as, for example, the fat tails of return distributions, and volatility clustering, as well as transient bubbles and crashes, which are connected with herding behavior. Some first results in that direction are reported in our previous papers [6,28], where the role of additional information, received by decision makers, is analyzed and it is shown that the amount of the additional information essentially influences the value of the quantum term. Further work on the generalization of the approach toward a dynamical theory of decision-maker societies is in progress.…”
Section: Discussionmentioning
confidence: 94%
“…In quantum theory, decoherence can be due to external as well as to internal perturbations and the influence of measurements [25][26][27]. And in QDT, decoherence can occur due to the accumulation of information [28]. The disappearance of the quantum term implies the transition to classical theory.…”
Section: Composite Quantum Measurements and Eventsmentioning
confidence: 99%
“…In the present section, we briefly sketch the basic scheme of QDT in order to remind the reader about the definition of quantum probability used in decision theory. The technical details have been thoroughly expounded in the previous articles [20]- [26], which allows us to just recall here the basic notions.…”
Section: Scheme Of Quantum Decision Theorymentioning
confidence: 99%
“…Our approach is based on Quantum Decision Theory (QDT), which we developed earlier [20]- [26]. There have been other attempts to apply quantum techniques to cognitive sciences, as is discussed in the books [27]- [30] and review articles [31]- [34].…”
Section: Introductionmentioning
confidence: 99%
“…It provides expressions for discount functions, employed in the theory of time discounting [45] and explains dynamical inconsistencies [5]. QDT also describes the influence of information and a surrounding society on individual decision makers [11,12]. While QDT has been developed to describe the behavior of human decision makers, it can also be used as a guide to create artificial quantum intelligence [6].…”
Section: Introductionmentioning
confidence: 99%